Audience Interpretation of Masculine Domination of Female Superhero Characters: A Reception Analysis Study on the Captain Marvel Film - Avina, Diyah Ayu Amalia; Ardhiaputri, Dhiesta (COMMENTATE: Journal of Communication Management, 2024)
This research explores how audiences interpret messages about masculine dominance in the portrayal of female superhero characters in the film Captain Marvel, emphasizing its elements of female masculinity. Employing a descriptive qualitative approach within an interpretive paradigm, the study applies Stuart Hall’s reception analysis method focusing on encoding and decoding. Audience interpretations are categorized into three hypothetical positions: dominant-hegemonic, negotiated, and oppositional. Data were gathered through in-depth interviews with six informants (three male, three female) selected via purposive sampling to ensure diversity and familiarity with the film. Preliminary interviews were followed by main interviews, during which six scenes were presented for interpretation. The collected data were transcribed, coded, and analyzed to determine the informants' positions. The findings show that audience interpretations of female masculinity in Captain Marvel are shaped by their individual experiences, knowledge, and backgrounds, leading to varied understandings of the film’s messages. These interpretations place informants within one of the three categories, with most audiences accepting the majority of the preferred readings.